Constitucionalização e humanização do processo : dimensão processual da dignidade como decorrência sistêmica da concepção, constitucional e democrática, do direito de agir para o Brasil do século XXI - Torres, Artur Luis Pereira (2014)
The scope of this study is to demonstrate the incompatibility between the regime of conditioning actions adopted by the Brazilian Code of Civil Procedure of 1973 (Eclectic theory of action) and the conception about the subject accepted thru the current 1988 Federal Constitution. This paper begins firstly by reviewing the ideology that underlies the formation of the current Brazilian State, making connections between the Constitutional State, Dignity and Civil Procedure, and secondly, by identifying the mainstay that gave rise to the emergence of so-called procedural science in the attempt to condemn the existing gap of the intended action of the State as a judge between yesterday and today. Immediately, after presenting considerations about the main theories of action, it moves over to the analysis of the country sub-constitutional legislation, which is complemented by the debate regarding the configuration or not, of the condition of the actions as a legal and procedural autonomous category. Finally, justifying the aforesaid incompatibility and bringing up the theoretical foundations inherent to this proposal, it strives for the recognition, despite the scope identified by the constitutional doctrine, of a procedural dimension of dignity, which consists of, mainly, in the substantial right of the contenders and the state's obligation to, if it is called up to intervene, to materially resolve the social conflicts